The earlier the gestational age, the greater the intensity of the intra-amniotic inflammatory response in women with preterm premature rupture of membranes and amniotic fluid infection by Ureaplasma species - OH, Kyung Joon (J Perinat Med, 2019)
OBJECTIVE: To determine the relationship between the intensity of the intra-amniotic inflammatory response and the gestational age at the time of diagnosis in cases with preterm premature rupture of membranes (PROM) and intra-amniotic infection caused by Ureaplasma spp. METHODS: A retrospective cohort study was conducted which included 71 women with preterm PROM and a positive amniotic fluid culture with Ureaplasma spp. Women with mixed intra-amniotic infections were excluded. The study population was classified into 3 groups according to gestational age: group 1, <26 weeks (extreme preterm PROM, n=17); group 2, 26.0–33.9 weeks (moderate preterm PROM, n=39); group 3, 34.0–36.9 weeks (late preterm PROM, n=15). The intensity of the intra-amniotic and maternal inflammatory response was compared among 3 groups. The intensity of the intra-amniotic inflammatory response was assessed by the concentration of amniotic fluid matrix metalloproteinase-8 (MMP-8) and white blood cell (WBC) count. The maternal inflammatory response was assessed by the concentration of C-reactive protein (CRP) and WBC count in maternal blood at the time of amniocentesis. RESULTS: 1) The median values of amniotic fluid MMP-8 concentration and WBC count were the highest in extreme preterm PROM group and the lowest in the late preterm PROM group (P < 0.001 and P=0.01, respectively); 2) the intensity of the maternal inflammatory response measured by maternal blood WBC count and CRP concentration was not significantly associated with gestational age at the time of diagnosis. CONCLUSION: The earlier the gestational age at the time of PROM, the higher the intensity of the intra-amniotic inflammatory response in women with preterm PROM and intra-amniotic infection caused by Ureaplasma spp.